Lethal Temperatures of a Neotropical Fish Relic in Patagonia, the Scale-Less Characinid Gymnocharacinus-Bergi - Ortubay, Silvia G. (1997)
Fil: Ortubay, Silvia G.. Dirección de Pesca. Ministerio de Economía de la Provincia de Río Negro; Argentina